A Review of the Molecular Mechanisms of Chemically-Induced Neoplasia in Rat and Mouse Models in National Toxicology Program Bioassays and Their Relevance to Human Cancer - Hoenerhoff, Mark J. (2009)
Tumor response in the B6C3F1 mouse, F344 rat, and other animal models following exposure to various compounds provides evidence that people exposed to these or similar compounds may be at risk for developing cancer. Although tumors in rodents and humans are often morphologically similar, underlying mechanisms of tumorigenesis are often unknown and may be different between the species. Therefore, the relevance of an animal tumor response to human health would be better determined if the molecular pathogenesis were understood. The underlying molecular mechanisms leading to carcinogenesis are complex and involve multiple genetic and epigenetic events and other factors. To address the molecular pathogenesis of environmental carcinogens, we examine rodent tumors (e.g., lung, colon, mammary gland, skin, brain, mesothelioma) for alterations in cancer genes and epigenetic events that are associated with human cancer. Our NTP studies have identified several genetic alterations in chemically induced rodent neoplasms that are important in human cancer. Identification of such alterations in rodent models of chemical carcinogenesis caused by exposure to environmental contaminants, occupational chemicals, and other compounds lends further support that they are of potential human health risk. These studies also emphasize the importance of molecular evaluation of chemically induced rodent tumors for providing greater public health significance for NTP evaluated compounds.